Potensi Bakteri Endofit Asal Tumbuhan Katemas (Euphorbia heterophylla L.) sebagai Pengendali Bakteri Penyebab Penyakit Busuk Lunak (Erwinia chrysanthemi) - Nurhakiki Nurhakiki; Elsie Elsie; Israwati Harahap (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Disease control in plants is generally controlled chemically using chemicals, but it can have a negative impact. One alternative to control plant diseases is to use microbial biological agents, namely endophytic bacteria. Endophytic bacteria from Euphorbia heterophylla L.Can be used as a controller for soft rot disease caused by Erwinia chrysanthemi. The purpose of this study was to isolate and determine the potential of endophytic bacteria from the katemas plant as a controller for soft rot disease caused by E. chrysanthemi. This study uses an experimental method. Isolation of antibacterial endophytic bacteria using surface sterilization method. Activity tests were carried out using the Kirby-Bauer method (disk diffusion). The parameter studied was to measure the inhibition zone formed around the paper disc using a caliper. The results of this study obtained 5 isolates of endophytic bacteria from the katemas plant which may control soft rot disease by E. chrysanthemi. Based on the research that has been done, it can be said that the results of the isolation of endophytic bacteria from the katemas plant obtained 5 isolates of endophytic bacteria with the inhibitory zone diameter of NK 1, NK 2, NK 3, NK 4 and NK 5 isolates of 1.1 mm each; 3.8mm; 2.0mm; 1.5mm and 22.5mm.